Statin-induced rhabdomyolysis: a complication of a commonly overlooked drug interaction. Issue 3 (14th March 2018) - Ezad, Saad; Cheema, Hooria; Collins, Nicholas
Abstract: Rhabdomyolysis is a well-documented side effect of statin therapy. This risk is increased with concurrent use of medications that inhibit cytochrome p450-3A4 (CYP3A4), such as macrolide antibiotics. We present the case of a 67-year-old patient who was commenced on clarithromycin on a background of simvastatin therapy, resulting in rhabdomyolysis. This case highlights the need for awareness of common drug interactions associated with statins. It also emphasizes the significance of commencing statins at a lower dose in new patients, and lastly, the importance of early recognition and management of rhabdomyolysis to prevent the development of complications.